Ionic liquid based ultrasonication-assisted extraction of essential oil from the leaves of Persicaria minor and conductor-like screening model for realistic solvents study - Ullah, H. (Zhongguo Kexueyuan - Chinese Academy of Sciences, 2017)
Ionic liquids (ILs) based ultrasonic-assisted extract has been applied for the extraction of essential oil from Persicaria minor leaves. The effects of temperature, sonication time, and particle size of the plant material on the yield of essential oil were investigated. Among the different ILs employed, 1-ethyl-3-methyli midazolium acetate was the most effective, providing a 9. 55 yield of the essential oil under optimum conditions (70:, 25 min, IL :hexane ratio of 7:10 (v / v), particle size 60-80 mesh). The performance of 1-ethyl-3- methylimidazolium acetate in the extraction was attributed to its low viscosity and ability to disintegrate the structural matrix of the plant material. The ability of 1-ethyl-3-methylimidazolium acetate was also confirmed using the conductor like-screening model for realistic solvents. This research proves that ILs can be used to extract essential oils from lignocellulosic biomass.